2019
DOI: 10.1002/cbic.201900031
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Libraries of Constrained Peptides

Abstract: Many therapeutic peptides can still be improved with respect to target specificity, target affinity, resistance to peptidases/proteases, physical stability, and capacity to pass through membranes required for oral delivery. Several modifications can improve the peptides’ properties, in particular those that impose (a) conformational constraint(s). Screening of constrained peptides and the identification of hits is greatly facilitated by the generation of genetically encoded libraries. Recent breakthrough bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…1,2 Recently, it was shown that they can also be used in phage-and yeast-display techniques to select for high affinity binders of human cell surface receptors with medical relevance. [4][5][6] In addition, lanthipeptide libraries have been successfully used to screen for inhibitors of protein-protein interactions. 7 Lanthipeptide biosynthesis starts with the ribosomal synthesis of a genetically-encoded precursor peptide (LanA) that is matured by an enzymatic processing machinery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, it was shown that they can also be used in phage-and yeast-display techniques to select for high affinity binders of human cell surface receptors with medical relevance. [4][5][6] In addition, lanthipeptide libraries have been successfully used to screen for inhibitors of protein-protein interactions. 7 Lanthipeptide biosynthesis starts with the ribosomal synthesis of a genetically-encoded precursor peptide (LanA) that is matured by an enzymatic processing machinery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rapid breakdown has limited the efficacy of many therapeutic peptides in complex biological fluids (de Vries et al, 2010). Cyclization can impose conformational constrains and then provide protection against proteolytic degradation as well as stabilize the conformation suitable for receptor binding (Bosma et al, 2019). Notably, a thioether link is more stable than a disulfide bond against hydrolytic decomposition, oxidation, or human serum (Tugyi et al, 2005; Rink et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…8b), the primary goal of this work was to demonstrate how NGS and coexpression of fluorescent proteins can be used to enhance data analysis of display libraries in general, rather than to provide an optimized peptide sequence for binding PLA. To further optimize affinity and specificity of peptides for PLA, it could be useful to employ a constrained peptide library, as they have been shown to improve both affinity and specificity [19]. Specificity for PLA, for instance over other plastics, can also be improved by incorporation of negative sorting steps in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in cysteine after sorting is particularly interesting since it could have both positive and negative effects on the peptide library. Cysteine could help constrain any structural component of the peptide that aids in binding affinity or specificity by creating disulfide bonds that increase rigidity [19]. However, when several cysteine residues are present in the library, unwanted intermolecular disulfide bonding could also occur, which could cause clumping of the displayed cells and interfere with isolation of individual peptides within the population for characterization.…”
Section: Analysis Of Library Diversitymentioning
confidence: 99%